1998
DOI: 10.1046/j.1365-3156.1998.00241.x
|View full text |Cite
|
Sign up to set email alerts
|

Cytopathic effects of Blastocystis hominis on Chinese hamster ovary (CHO) and adeno carcinoma HT29 cell cultures

Abstract: SummaryBlastocystis hominis isolates from asymptomatic carriers and symptomatic patients were cultured in vitro, purified from the co-cultivated bacterial flora and tested for cytopathic effects on monolayers of Chinese Hamster Ovary (CHO) cells and Adeno Carcinoma HT29 cells. In the case of the CHO cells, living B. hominis cells and B. hominis cell lysates were able to cause significant cytopathic effects, which were dependent on the concentration of cells employed. Destruction of the cell monolayers was obse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0
1

Year Published

2005
2005
2012
2012

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 21 publications
1
15
0
1
Order By: Relevance
“…The ability of Blastocystis to kill host cells in vitro was observed previously (48), but the mechanism of cell death was not noted. In clinical cases of Blastocystis infections, evidence of intestinal epithelium damage was documented (12), but specific features of cell apoptosis were not reported.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…The ability of Blastocystis to kill host cells in vitro was observed previously (48), but the mechanism of cell death was not noted. In clinical cases of Blastocystis infections, evidence of intestinal epithelium damage was documented (12), but specific features of cell apoptosis were not reported.…”
Section: Discussionmentioning
confidence: 89%
“…In vitro studies have demonstrated that Blastocystis is capable of causing significant cytopathic effects on Chinese hamster ovary cells (48). Recently, a variety of intestinal pathogens were found to induce apoptosis in intestinal epithelial cells, and their association with pathogenicity was suggested (11,14,20,22,29,46).…”
mentioning
confidence: 99%
“…Cells and lysates of Blastocystis spp. isolated from asymptomatic carriers and symptomatic patients induced cytopathic effects on Chinese hamster ovary cells but not in HT-29 colonic epithelial cells (286). The lack of cytopathic effects on HT-29 was validated in a later study, which was also absent in T-84 cell lines exposed to Blastocystis (139).…”
Section: In Vitro Studiesmentioning
confidence: 89%
“…A few studies have sought to investigate the effects of Blastocystis spp. on mammalian cell cultures (139,191,192,286). Cells and lysates of Blastocystis spp.…”
Section: In Vitro Studiesmentioning
confidence: 99%
“…Endoscopic and permeability studies of the intestine in a cohort study of Blastocystis-infected immunocompetent individuals failed to find any significant intestinal inflammation or impairment of the intestinal permeability barrier (Zuckerman et al, 1994). Fresh Blastocystis isolates, though, have been demonstrated to cause significant cytopathology of Chinese hamster ovary cells (CHO), adenocarcinoma HT-29 cells and rat intestinal epithelia (IEC-6) cells in culture (Puthia et al, 2006;Walderich et al, 1998). Metronidazole, paromomycin and ketoconazole have been used as therapeutic agents with mixed success (Zierdt et al, 1983;Dunn & Boreham, 1991;Haresh et al, 1999;Nanba et al, 2003).…”
Section: Introductionmentioning
confidence: 99%